Ethanolic Fermentation Efficiency of Seaweed Solid Waste Hydrolysates by Saccharomyces cerevisiae - Pujoyuwono Martosuyono; Ifah Munifah; Gesty Aulia Ningrum (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2016)
The objective of this research was to determine the saccharification and the fermentation efficiency of seaweed solid waste hydrolysate by Saccharomyces cerevisiae (Accession number 3012.254) in anaerobic condition. The optimum saccharification yield of acid pretreated waste (40.93±1.72)% was obtained after 48 hours with  saccharification rate of (0.51±0.02) g/l.h. Higher yield was shown by NaOH pretreated waste (67.29±1.24)% after 24 hours with saccharification rate of (0.81±0.06) g/l.h. The fermentation of enzymatic hydrolysates of acid and alkali pretreated samples by S. cerevisiae produced a maximum of 7.52±0.24 g/l and 14.5±0.54 g/l ethanol respectively after 72 hours fermentation. Maximum ethanol yield was 0.31±0.03 g/g and 0.40±0.02 g/g sugar respectively for acid and alkali pretreated samples. The ethanol yields showed that alkali pretreated sample produces higher conversion substrate ratio (80% of theoretical yield) compared to acid pretreated sample (62% of theoretical yield).